1997
DOI: 10.1103/physrevb.56.1017
|View full text |Cite
|
Sign up to set email alerts
|

Structural model for the Si(111)-4×1-In reconstruction

Abstract: A -bonded-chain-stacking-fault (-SF͒ model is proposed for the Si͑111͒4ϫ1-In surface structure. The model incorporates 4ϫ1 Si͑111͒ substrate reconstruction consisting of the sixfold Si rings in the faultedunfaulted sequence connected through fivefold and sevenfold Si rings. Indium atoms ͑0.75 ML͒ reside above sixfold and fivefold Si rings while sevenfold Si rings form -bonded chains between In ridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…The room-temperature (RT) 4×1 structure of the In/Si (111) confirmed by ab-initio calculations [3,4,5] which reproduce the scanning tunneling microscopy (STM) images [6,7], and the main features of the band structure.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The room-temperature (RT) 4×1 structure of the In/Si (111) confirmed by ab-initio calculations [3,4,5] which reproduce the scanning tunneling microscopy (STM) images [6,7], and the main features of the band structure.…”
Section: Introductionmentioning
confidence: 89%
“…The electronic correlations and the coupling between electronic and structural degrees of freedom are enhanced in one-dimension and, as a consequence, several electronic and structural phase transitons are observed in these systems as the temperature is decreased. A nice example of this behavior is found in the In/Si(111) system, which exhibits a 4×1 → 4×2 → 8×2 structural transition accompanied by a metal-insulator electronic transition.The room-temperature (RT) 4×1 structure of the In/Si (111) confirmed by ab-initio calculations [3,4,5] which reproduce the scanning tunneling microscopy (STM) images [6,7], and the main features of the band structure.At RT the system presents three metallic surface bands with similar dispersion [8]. However, when the temperature is lowered below ∼ 130 K [9] photoemission shows the formation of a band gap.…”
mentioning
confidence: 89%
“…1 Adsorbed hydrogen was found to displace the indium atoms. [9][10][11] Filled-state STM images of the hydrogenated substrate show a (4×1) reconstruction with straight chains instead of the broad zigzag chains on the indium-terminated surface. 9-11 From these observations and results found in the literature Saranin et al 9 proposed a structural model.…”
mentioning
confidence: 99%
“…[9][10][11] Filled-state STM images of the hydrogenated substrate show a (4×1) reconstruction with straight chains instead of the broad zigzag chains on the indium-terminated surface. 9-11 From these observations and results found in the literature Saranin et al 9 proposed a structural model. This model as well as the model derived by Collazo-Davila et al 12 by applying direct methods to transmission electron diffraction (TED) data are at variance with the x-ray photoelectron spectroscopy (XPS) results of Abukawa et al 13 Since the core-level spectra did not show peaks corresponding to surface silicon atoms a complex substrate reconstruction can be ruled out.…”
mentioning
confidence: 99%
“…This system was characterized structurally [5][6][7][8][9] and electronically [10,11]. In these works it was found that the In atoms were organized into linear chains of atoms, and that the electronic properties appeared to be highly anisotropic, with metallic behavior indicated by band crossings of E F along the chains.…”
Section: X1 Reconstruction: 1deg [4]mentioning
confidence: 99%